Rickettsial infection in equids, opossums and ticks in the municipality of Monte Mor, state of São Paulo, Brazil - Ueno, Tatiana Evelyn Hayama; Cutolo, André Antonio [UNESP]; Martins, Thiago Fernandes; Moraes-Filho, Jonas; de Azevedo, Sérgio Santos; Labruna, Marcelo Bahia (FapUNIFESP (SciELO), 2020)
The aim of this study was to investigate rickettsial infection in equids, opossums and ticks in the municipality of Monte Mor, a place where a Brazilian spotted fever case occurred in 2005. In addition, characteristics possibly associated with seropositivity in horses were analyzed. Serum samples from horses, mules and opossums (Didelphis albiventris) were subjected to indirect immunofluorescence assay (IFA) against Rickettsia rickettsii. The ticks collected from the animals were identified and Amblyomma sculptum ticks from the equids were tested using PCR for Rickettsia spp. Anti-R. rickettsii antibodies were detected in 22.6% (14/62) of the horses, none of the mules and 21.7% (5/23) of the opossums. Among the variables analyzed, only age > 12 years showed a statistically significant association with seropositivity among horses. All of the 166 A. sculptum ticks tested using PCR were negative. The results showed that rickettsiae of the spotted fever group was circulating in the municipality of Monte Mor when the samples were collected and indicate a need for surveillance of Brazilian spotted fever in this region.
Infecção por rickettsia spp. Em equídeos, gambás e carrapatos do município de Monte Mor, Estado de São Paulo, Brasil
Keywords: Didelphis; Equine; Rickettsiales; Spotted fever; São Paulo